ANALISIS PERTUMBUHAN EKONOMI DAN DISTRIBUSI PENDAPATAN KABUPATEN BONE BOLANGO - Harijono Imbran (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to analyze the economic growth and income distribution of Bone Bolango Regency. This study uses a descriptive quantitative approach and the data source used is secondary five-year time series data. The analytical tool used is the analysis of economic growth and the Williamson index equation.The results showed that the economic growth of Bone Bolango Regency was very volatile with an average growth of above 6%. The decline was due to low macroeconomic productivity. The results of the Williamson Index analysis show that the average distribution of income in each sub-district is still relatively low. This is evidenced by the index value is still close to 1. The larger the index, the greater the income inequality that occurs.